Implementasi Kebijakan Perizinan dan Pemberitahuan Kegiatan Masyarakat Pada Kepolisian Resort (POLRES) Kota Baubau - Farid Yusuf Nur Achmad (Kybernan: Jurnal Studi Kepemerintahan, 2016)
This studywas conducted todetermine and analyze the implementation of the licensing policies and notices of community activities in Baubau City Police and communication factors, resources, disposition, and structure influence the implementation of the licensing policies and notices of community activities in Police Baubau. The results showed that the licensing policies and notices activities of people implemented by (a) Providea receipt notice (b) To coordinate with the responsible delivery of opinions in the Public (c) To coordinate with the leadership, the agency/institutionwhich is the goal of delivering the opinion (d) Prepare securing alocation and route that passed.(e) responsible for protecting the participants in the delivery of public opinion (f) responsible for organizing security and factors factors that influence the implementation of the licensing policies and noticesof community activities are: (1) Communication; (2) Resources (3) Disposition; and (4) Organizational Structure.